A database for therapy evaluation in neurological disorders application in epilepsy. - Kirlangic, M.E.
Due to the high diversity of cases and the variety of treatment modalities, the information to be managed and processed in therapy evaluation is excessive in many neurological diseases. Additionally, in order to gain more insight into, not only the disorders, but also the applied therapies, more objectivity is requested in clinical practice. Therefore, in this study, a database system is designed for assisting therapy evaluation in neurological diseases. A sample implementation is accomplished for structuring and managing the information accessible for different treatment modalities available for epilepsy. The first application of the developed database system for clinical use in epilepsy is tested with selected quantitative parameters extracted from electrophysiological signals of epilepsy patients who receive neurotherapy as a complementary treatment to the pharmacological therapy, as well as of voluntary control subjects. The system contributes to the automation of statistical analysis for therapy planning, monitoring, and evaluation. It is extendible for other disorders such as attention deficit hyperactivity disorder, depression, and sleep disorders.
Keywords: Attention deficit hyperactivity disorder; Depression; Electrophysiological signal; Epilepsy; Neurological disorders; Pharmacological therapy; Sleep disorder; Therapy evaluation database; Therapy monitoring; Therapy planning